Intrusion Detection System Based On Flows Using Machine Learning Algorithms - Kakihata, E. M.; Sapia, H. M.; Oikawa, R. T.; Pereira, D. R.; Papa, J. P. [UNESP]; Alburquerque, V. H. C.; Silva, F. A. (Ieee-inst Electrical Electronics Engineers Inc, 2017)
The use of technology by different types of devices generates a large flow of confidential and personal information. Referencing this situation, it is necessary to use computer security tools, such as Intrusion Detection Systems (IDS). This work presents an IDS that can perform the flow-based analysis (netflow). The first step of this research conducted an analysis on flows previously collected and properly detected three different types of attacks. In the second step, the flows were organized to be used in machine learning algorithms.
Keywords: intrusion detection system; netflow; machine learning